Risks of Skin, Hair, and Nail Supplements - Emily K. Burns; Ariadna Perez-Sanchez; Rajani Katta (Mattioli1885, 2020)
Skin, hair, and nail supplements, sometimes referred to as "beauty supplements" or "ingestible skin care", are a large and growing industry. These products may contain vitamins and minerals, sometimes in very high doses. They may also contain herbs, hormones, microbes, or animal derivatives such as fish oils and collagen powders. Dietary supplements are regulated as foods, not drugs, by the U.S. Food and Drug Administration. Therefore, manufacturers do not need to provide any proof of safety, efficacy, or quality prior to sale. This is of serious concern, as many adverse effects due to supplement components have been reported. The potential risks cover multiple categories. These include acute toxicities such as choking, as well as chronic toxicities, such as increased risk of diabetes. Teratogenicity and interaction with drugs and laboratory testing have been documented in research studies. Other risks include potentially increased risk of cancer with long-term use, allergic reactions, and others. It is vital that physicians educate their patients on these risks. As no post-marketing surveillance programs are required for supplements, our understanding of supplement risks is incomplete. Physicians should be wary of these risks and encourage further research and regulation.